2014
DOI: 10.1038/srep06175
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 expression in long-term germ stem cells

Abstract: Asingle cells in undifferentiated spermatogonia are considered to be the most primitive forms of germ stem cells (GSCs). Although GFRα1 is thought to be a marker of Asingle cells, we found that Bmi1High is more specific than GFRα1 for Asingle cells. Bmi1High expression in Asingle cells is correlated with seminiferous stages, and its expression was followed by the proliferative stage of Asingle GSCs. In contrast, GFRα1 expression was seminiferous stage-independent. Fate analyses of EdU-positive Bmi1High-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 35 publications
7
65
1
1
Order By: Relevance
“…4C). These data are consistent with previous studies that showing that SSCs follow a neutral competition model (6,31,33,34), although additional, detailed analyses are needed to validate this model further.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4C). These data are consistent with previous studies that showing that SSCs follow a neutral competition model (6,31,33,34), although additional, detailed analyses are needed to validate this model further.…”
Section: Discussionsupporting
confidence: 91%
“…4C). These results are consistent with a neutral competition model in which tissue stem cells are routinely lost and replaced in a stochastic manner, as previously demonstrated by the use of specific Cre lines of GFRα1, Ngn3, and Bmi1 in the testis (6,31,33,34).…”
Section: Multiple Gfrα1supporting
confidence: 90%
“…Consistent with this model, post-transplantation colony formation and regeneration assays confirmed that the vast majority of stem cell activity is restricted to the population of undifferentiated (Kit-negative) spermatogonia (Shinohara et al, 2000). More recently, the identification of genetic markers that are enriched in or restricted to A s spermatogonia, including the transcriptional repressor ID4, the polycomb complex protein Bmi1 and the paired-box protein Pax7, allowed the potency of individual A s cells to be assessed (Aloisio et al, 2014;Komai et al, 2014;Oatley et al, 2011). These studies confirm that at least a fraction of A s cells retains long-term self-renewal potential, lending further support to the A s model paradigm.…”
Section: Examples Of Dynamic Stem Cell Heterogeneity Mammalian Spermamentioning
confidence: 63%
“…This concept of a gradient of expression distinguishing SSC and progenitor populations is likely to be applicable to many molecules that have been considered SSC markers. In corroboration of this concept, a recent study utilized lineage tracing to show that SSCs are present in the BMI1 highly expressing population, whereas the population with lower expression is mostly progenitors (Komai et al, 2014).…”
Section: Discussionmentioning
confidence: 92%
“…Two major approaches for assigning stem cell function to specific populations are lineage tracing and transplantation. Although several cell populations, such as those marked by GFRA1 (Ebata et al, 2005;Grisanti et al, 2009;Hara et al, 2014), PAX7 (Aloisio et al, 2014), BMI1 (Komai et al, 2014) or NEUROG3 (Nakagawa et al, 2010) expression, have been identified as containing at least some SSCs using one of the approaches, the ID4 expressing population is the only one reported to date to be enriched for SSCs using both lineage tracing and transplantation (Chan et al, 2014;Sun et al, 2015). Moreover, in the current study we demonstrate through limiting dilution transplantation analysis that the ID4-EGFP Bright population is mostly, if not purely, SSCs.…”
Section: Discussionmentioning
confidence: 99%